A review about the concept of metaphorical aspects of annex buildings. Issue 1 (1st January 2018) - Allahmoradi, Mitra
Abstract: Architecture as the making of metaphors is the study of effective design. One of the roles of conceptual metaphor is that it permits the user to form the concept of the virtual world from the aspect of time and the motion in the physical dimension of the architecture world. Utilizing metaphor to distinguish the secret attributes of the content is an indicative factor. The historical surroundings have contained and will contain during the time of natural actions and interventions from the human. One of the most important concerns in the preservation operation is the addition to the historical structures. It is the role of new and modern architecture styles to indicate the importance and architectural significance of historical structures. One of the main concerns in the field of conservation is attributed to the relationship between the historical structures and contemporary modern additions. In most cases, the modern additions influence the primary building to display its mental image to the users. The present research aims to study the metaphoric viewpoints of new additions to historic buildings in the historical context and recognize the appropriate balance between these two concepts. For this aim, two case studies were analyzed with the methodology that considers the metaphoric aspects of the new additions.